Sea cucumbers, Holothuria arguinensis and H-mammata, from the southern Iberian Peninsula: variation in reproductive activity between populations from different habitats - Marquet, Nathalie (2019)
New fisheries in the western Mediterranean and north eastern Atlantic target the sea cucumbers Holothuria arguinensis and H. mammata; however, lack of biological information hinders management decisions. Here, the reproductive biology of populations the two species was investigated in the southern Iberian Peninsula. Different populations located along a narrow latitudinal range displayed the same general reproductive pattern of summer-autumn spawning. However, significant differences in size, gonadal production and maturity profile between locations suggests the influence of site-specific factors. In Sagres and Ria Formosa H. arguinensis individuals were larger and had larger gonads than in Olhos de Agua, which had relatively more immature animals. The spawning and active gametogenesis periods were also longer in Sagres, possibly linked to specificity of food availability and tidal conditions. Ria Formosa also had larger H. mammata individuals with larger gonads than in Murcia and Olhos de Agua, possibly reflecting differences in feeding activity in different substrates (muddy/sandy vs rocky). Gametogenesis in H. arguinensis may be triggered by decreasing photoperiod and temperature, and spawning by increasing temperature. Altogether, these results, which include fecundity and size at first maturity, provide an important basis for the scientific management of sea cucumber fisheries in the region. (C) 2017 Elsevier B.V. All rights reserved.